2019
DOI: 10.1002/pi.5832
|View full text |Cite
|
Sign up to set email alerts
|

Porous organosilicone modified gelatin hybrids with controllable and homogeneous in vitro degradation behaviors for potential application as skin regeneration scaffold

Abstract: This work aims at investigating intensively the effects of organosilicone species and their dosage on the physicochemical and particularly the in vitro degradation properties of gelatin hybrids. We prepared various porous organosilicone modified gelatin hybrids with epoxy-polydimethylsiloxane (PDMS) and/or glycidoxypropyltrimethoxysilane (GPTMS) and further systematically investigated their degradation behaviors in simulated physiological environments. It was found that the chemical composition, thermal stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…And the asymmetric stretching vibration of CH 2 appeared at 2950 cm −1 , while peaks at 1634, 1538, and 1450 cm −1 are corresponding to CO stretching vibration, NH bending vibration (amide II), and CH bending vibration, respectively 28,29 . In addition, from the FT‐IR spectrum of SiO 2 aerogel, it can be seen that the peak appeared at 2950 cm −1 is the characteristic peak of CH, and the peak around 1253 cm −1 is the stretching vibration of SiC, indicating that SiCH 3 is successfully grafted to the surface of the silica aerogel by HMDS 30,31 . The peak around 1084 cm −1 can be attributed to the stretching vibration of SiOSi bond, and the peak at 950 cm −1 can be attributed to the bending vibration of the SiOH group.…”
Section: Resultsmentioning
confidence: 92%
“…And the asymmetric stretching vibration of CH 2 appeared at 2950 cm −1 , while peaks at 1634, 1538, and 1450 cm −1 are corresponding to CO stretching vibration, NH bending vibration (amide II), and CH bending vibration, respectively 28,29 . In addition, from the FT‐IR spectrum of SiO 2 aerogel, it can be seen that the peak appeared at 2950 cm −1 is the characteristic peak of CH, and the peak around 1253 cm −1 is the stretching vibration of SiC, indicating that SiCH 3 is successfully grafted to the surface of the silica aerogel by HMDS 30,31 . The peak around 1084 cm −1 can be attributed to the stretching vibration of SiOSi bond, and the peak at 950 cm −1 can be attributed to the bending vibration of the SiOH group.…”
Section: Resultsmentioning
confidence: 92%
“…), although have excellent mechanical properties, their bioactivity, and antiinfection ability are poor. Porous materials prepared from natural polymers (chitosan, 8 gelatin, 9 etc.) have good bioactivity, but most of them have poor mechanical properties or few raw materials, which are difficult to be widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, poor mechanical strength, high hydrophilicity and rapid degradability greatly limit its effective and wide application . Our previous studies demonstrated that the incorporation of polydimethylsiloxane (PDMS) chains in GE molecules could improve the mechanical flexibility, porous structure and degradation resistance, but the proposed GE‐based materials are simply designed as a single‐layer film . In contrast, silicone rubber (SR), a typical synthetic material, has inherent hydrophobicity, high flexibility and good biocompatibility but poor biodegradability .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Our previous studies demonstrated that the incorporation of polydimethylsiloxane (PDMS) chains in GE molecules could improve the mechanical flexibility, porous structure and degradation resistance, but the proposed GE-based materials are simply designed as a single-layer www.soci.org W Du, Z Zhang, Z Li film. [17][18][19] In contrast, silicone rubber (SR), a typical synthetic material, has inherent hydrophobicity, high flexibility and good biocompatibility but poor biodegradability. 20,21 As known from the self-stratification strategy, the combination of GE or modified GE and SR is a feasible approach to fabricate a porous bilayer membrane, thus expressing their respective advantages.…”
Section: Introductionmentioning
confidence: 99%